Photoionization cross-section of isotropic defects or impurity centers in isolators. (12th September 2016) - Lima, H.; Batista, J. V.; Couto dos Santos, M. A.
Abstract: An analytical expression to calculate the photoionization cross-section of isotropic defects or impurity centers is being proposed by using the time-dependent perturbation theory. The ground-state wave function of the electron captured in the impurity state is described by a three-dimensional isotropic harmonic oscillator and the electron excited state in the continuum conduction band is described by a plane wave. The expression has been obtained considering all multipoles terms in the Hamiltonian, and that the radiation field which interacts with electrons is semi-classical and linearly polarized. This approximation is assumed because the effects of the linear contribution are dominant. The available data of the Al2 O3 :C and Lu2 SiO5 :Ce systems are in good agreement with our predictions. Such satisfactory comparison is a strong indication that the present model can be used to provide good predictions of the photoionization cross-section in several areas.